The Effectiveness of Local Banjar Board Media in Enhancing Letter Recognition in Children Aged 5–6 Years - Hervina, Mimin; Rivo Panji Yudha (Kirana Publisher (KNPub), 2025)
Early literacy development, particularly letter recognition, plays a crucial role in forming reading readiness in early childhood. This study aimed to examine the effectiveness of the Banjar Local Board Media in improving letter-recognition skills among children aged 5–6 years. This experimental research employed a one-group pretest–posttest design involving 17 kindergarten children at TK Perjuangan Bunda, Tabalong, Indonesia. Data were collected using a 27-item letter-recognition test measuring the ability to identify letter shapes, associate letters with sounds, and the form of simple written letters. The treatment consisted of four learning sessions integrating Banjar cultural elements through picture–letter associations, phonological activities, and interactive board manipulation. The data were analyzed using descriptive statistics and paired t-test to determine significant differences between pretest and posttest scores. Findings revealed a substantial increase in children's letter-recognition ability, demonstrated by a rise in average scores from 51 (pretest) to 77 (posttest), indicating a 43.3% improvement after the intervention. These results suggest that integrating cultural-based media provides meaningful and enjoyable learning experiences that effectively enhance early literacy competencies. The study contributes to the literature on culturally responsive teaching in early childhood education and emphasizes the relevance of local wisdom in strengthening learning engagement and outcomes. Future research is advised to involve larger samples and employ comparative experimental designs to broaden generalization and strengthen evidence of effectiveness.